Factors Determining the Use of Public Transportation Among Cross-Generational Tourists in Yogyakarta - Tiara Sisky Wulansari; Leony Anggelina Willyanto; Siti Rahayu; Fitri Novika Widjaja (Universitas KH. Abdul Chalim Mojokerto, 2025)
The utilization of public transportation could be affected by several factors such as motivation, negotiation, and constraints so it could be the determining factor in the decision-making process to use public transportation. This research aims to know whether motivation, negotiation, and constraints affect public transportation use for tourists in Yogyakarta. The researcher used quantitative research and samples were taken by distributing questionnaires online through the Google Form platform for the tourists. The data process was done by using PLS-SEM. The result of this research showed that motivation and negotiation have a significant impact on public transportation use. Constraints did not significantly affect public transportation use. This research contributes academically to add literature regarding the public transportation users behavior from three generations in Indonesia with a quantitative approach.